2015
DOI: 10.1038/ncomms9348
|View full text |Cite
|
Sign up to set email alerts
|

Coordination templated [2+2+2] cyclotrimerization in a porous coordination framework

Abstract: Controlling chemical reactions by the supramolecular confinement effects of nanopores has attracted great attention. Here we show that open metal sites in porous coordination frameworks can constitute more powerful and strict templates for precision syntheses. A Fe(III) dicarboxylate framework functionalized with triangularly arranged metal sites is used to accomplish [2+2+2] cyclotrimerization reactions for organonitrile, alkyne and alkene monomers bearing a geometrically suitable pyridyl group. In situ singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 43 publications
1
64
1
Order By: Relevance
“…For comparison, we also sought to use 4, 4′‐dipyridyldisulfide (dpds) as PPA, but found that the same dps‐pacs could be obtained. These results showed that MIL‐88 type structure might have better fit for dps …”
Section: Figurementioning
confidence: 77%
“…For comparison, we also sought to use 4, 4′‐dipyridyldisulfide (dpds) as PPA, but found that the same dps‐pacs could be obtained. These results showed that MIL‐88 type structure might have better fit for dps …”
Section: Figurementioning
confidence: 77%
“…Wei et al . used the PSE&I strategy to remove and insert ligands in MIL‐88 . The regular hexagonal channels in MIL‐88 make the open metal sites formed after the removal of the coordinated water molecules in the Fe 3 (μ 3 ‐O) cluster by heating.…”
Section: Post‐synthesis Modification (Psm)mentioning
confidence: 99%
“…The trimeric products (MIL‐88B) with 4‐pyCN (a), 4‐pyC 2 H (b), and 4‐pyC 2 H 3 (c) as monomers. Reproduced with permission . Copyright © 2015, Springer Nature.…”
Section: Post‐synthesis Modification (Psm)mentioning
confidence: 99%
“…This alignment is ideally suited to fix three molecules in the ideal configuration to facilitate trinuclear reactions such as [2 + 2 + 2] cycloadditions. 31 The power of this approach was illustrated by the successful incorporation and trimerization of three different kinds of linker: 4-cyanopyridine, 4-ethynylpyridine, and 4-vinylpyridine. Heating of the ligand exchanged MOF initiates the [2 + 2 + 2] cycloaddition reactions of the incorporated molecules in the pores which leads to the formation of triazine, benzene, and cyclohexane moieties, respectively ( Figure 4 c–e).…”
Section: Precise Spatial Arrangement Of Ligands In Mofsmentioning
confidence: 99%